Design Phase Delay Control for Soft Starting 3 Phase Induction Motor - Kukuh Widarsono; Moh. Jauhari; Beny Guzman Raiz; Helmy Sahirul (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
Induction motor is one type of electric machine that is widely used both in household consumers and industrial players. However, induction motors have drawbacks, namely starting currents that can reach 5-7 times the nominal current, of course this can lead to reduced life time of other electrical equipment and the possibility of shutdown or trip is very large. This research proposes a new modeling to create a soft starting system to reduce the 3 phase induction motor start current. This system was built with the help of a Phase Delay Control power electronics circuit with the main component, Triac, which functions to regulate the input voltage of a 3 phase induction motor and a contactor whose function is to move the 3 phase induction motor power supply from the soft starting system to the PLN source directly if, The input voltage is the same as the nominal voltage. The output of these processes is the Triac ignition angle, so during the starting process, the induction motor will receive an input voltage in stages from the smallest to reach its nominal voltage. Thus the results of testing the soft starting system that is designed to have a maximum current value at the start of 2.45 A or 77.58% lower than the start current using the DOL method with a value of 10.93 A at no-load conditions and 7.41 A or 34.19% lower than the motor starting current with the DOL method with a value of 11.31 A when the motor is loaded.Keywords: phase delay control, soft starting, three phase induction motor.